Destination Image: International Tourists’ Perception of Bali’s Cultural Landscape as UNESCO’s World Heritage Site - Dalimunthe, Gallang Perdhana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper aims to find out the perception of foreign tourists towards the Subak Cultural Lanscape as the UNESCO’s World Heritage Site. Analysis of destination image can assist related parties in developing the destination according to its image and characteristics. Destination Image is a topic that has been extensively investigated in the field of tourism marketing, it is the overall impression obtained by individuals from a particular tourist destination. This overall impression is obtained from the perception of visitors related to the quality of the tourist attractions. Descriptive statistics is used to gather the information of the foreign tourists perception about the destination image. It can be seen that tourists feel that they do not get the interesting cultural activities offered by the organizers, even though this destination sells its big name as a cultural landscape that is recognized by UNESCO.